Suspensions Flow in Tree Structures: Pulmonary Deposition of Inhaled Aerosols - Miguel, A. F. (2017)
The respiratory tree is a natural porous structure that is unique, challenging, and high-value media to study. It has long been recognized that the pattern of particle deposition in the respiratory tree affects how deeper aerosols penetrate in the deeper zones of tree and, therefore, the pathogenic or therapeutic potential of inhaled aerosols. In this paper, particle deposition in a tree network made of glass fiber tubes that corresponds to the proximal-conducting zone of the respiratory tract [5,6] is studied experimentally. The effect of particle size and breathing frequencies on detailed deposition patterns of monodispersed microspheres between 0.2-12 microns is examined.